Simultaneous Quantification of Propylthiouracil and Its N-β-d Glucuronide by HPLC-MS/MS: Application to a Metabolic Study - Min Li; Qingfeng He; Li Yao; Xiaofeng Wang; Zhijia Tang; Xiao Zhu; Hai-Shu Lin; Xiaoqiang Xiang (Pharmaceuticals, 2021)
Propylthiouracil (PTU) is commonly prescribed for the management of hyperthyroidism and thyrotoxicosis. Although the exact mechanism of action is not fully understood, PTU is associated with hepatoxicity in pediatric population. Glucuronidation mediated by uridine 5′-diphospho-glucuronosyltransferases (UGTs), which possess age-dependent expression, has been proposed as an important metabolic pathway of PTU. To further examine the metabolism of PTU, a reliable HPLC-MS/MS method for the simultaneous quantification of PTU and its N-β-D glucuronide (PTU-GLU) was developed and validated. The chromatographic separation was achieved on a ZORBAX Extend-C18 column (2.1 × 50 mm, 1.8 μm) through gradient delivery of a mixture of formic acid, methanol and acetonitrile. The electrospray ionization (ESI) was operated in its negative ion mode while PTU and PTU-GLU were detected by multiple reaction monitoring (MRM). This analytical method displayed excellent linearity, sensitivity, accuracy, precision, recovery and stability while its matrix effect and carry-over were insignificant. Subsequently, the in vitro metabolism of PTU was assessed and UGT1A9 was identified as an important UGT isoform responsible for the glucuronidation of PTU. The information obtained from this study will facilitate future mechanistic investigation on the hepatoxicity of PTU and may optimize its clinical application.